Dissertating during a pandemic : narratives of success from scholars of color - Goings, Ramon B.; Cupid, Sherella; Gardner, Montia; Tomlin, Antione D. (Emerald Publishing Limited : Information Age Publishing, Inc., 2022)
Dissertating During a Pandemic: Narratives of Success from Scholars of Color examines the experiences of doctoral students of color writing the dissertation currently and those who successfully defended their dissertation after the onset of COVID-19 and subsequent shutting down of college campuses in March 2020. While we know that scholars of color experience many barriers to completing the dissertation process prior to COVID-19 such as being in racist academic environments and being engaged in research areas that may not be supported by predominantly White faculty, it is important to consider how scholars of color are managing the dissertation process during this pandemic.We approach this book from an asset-based approach where chapter authors are approaching both the challenges and opportunities they have experienced due to being a dissertation writer during the pandemic. Chapter authors also provide poignant feedback on how professors can be supportive to their needs as dissertation writers. One especially important contribution of this book is that our authors are from a variety of disciplines including: education, social work, psychology, African American studies, and sociology. Additionally, chapter authors are doctoral candidates (and recent graduates) at predominantly White institutions, historically Black colleges and universities, and online universities. Given the breadth of institution types each chapter will provide poignant suggestions for doctoral students across the nation as well as for faculty who are looking to better understand the dissertation writer experience to support their own students.Because of the novelty of COVID-19, little is known about how doctoral students engaged in writing the dissertation during COVID19 are adapting. Moreover, there is little information available for professors on how to support their doctoral students during these unprecedented times. Thus, Dissertating During a Pandemic: Narratives of Success from Scholars of Color is positioned to be a must read for professors looking to support their doctoral student advisees as well as for doctoral students who are looking for strategies to navigate the dissertation process during the pandemic and beyond.
Keywords: Minority doctoral students -- United States.; Dissertations, Academic -- United States.; Doctor of philosophy degree -- United States.; Social distancing (Public health) and education -- United States.; COVID-19 (Disease); COVID-19 Pandemic, 2020-2023.; Education -- Schools -- Levels -- Higher.; Higher education, tertiary education.; elektronické knihy; electronic books